The teaching of Statistics presented in the curricular materials of the first three years of Elementary School - Martins, Priscila Bernardo (2020)
The present study aims to analyze whether the activities proposed in the Mathematics curriculum materials, called Caderno do Aluno, Educação Matemática nos Anos Iniciais (EMAI) project, from the first three years of Elementary School, employed by the State Education Network of São Paulo, allow the development of Literacy Student statistics. Thus, we opted for documentary analysis from the perspective of Bardin (2016). As a result, it was possible to observe that the analyzed activities contribute to the promotion of the development of Statistical Literacy, by guiding students in understanding statistical information, organizing data and representing tables. However, it was observed that the acquisition of Statistical Literacy requires other skills that the activities do not encourage as much — the ability to argue, the construction and representation of graphs and tables, the appropriation of statistical vocabulary and the competence to produce texts about their interpretations.